ODOROLOGICAL EXAMINATION IN THE CRIME INVESTIGATION PROCESS. THEORY, METHODS AND PRACTICE - Davronov Atobek Ravshanovich (Scholar Express Journals, 2023)
In this study, the author considers a specific method of forensic science, this is an odorological examination. Modern theoretical and practical problems related to the preparation and conduct of an odorological examination are considered. In addition, this article conducts a comparative study of odor samples, the possibility of which is based on the individuality of the smell of each person. The main task of the expert is to establish the presence of odor traces of specific people suspected of committing crimes. During the examination, smelling traces of human metabolism are examined. These traces can accumulate on various items: on clothes, shoes, hats, etc. Indeed, such objects can store the smell of the owner for a very long time, sometimes for several years. The smell can also be stored in dried blood. In this case, either the object itself with the stain is sent for examination, or a scraping is done, and if the blood is on a porous surface, then a wash is done. In addition to the above, the author came to the conclusion that odorous traces remain on different objects for different times: for example, on a cigarette butt or a knife handle - up to several hours, and if the offender has been in contact with the thing for more than half an hour, then the smell persists for up to three days.
Keywords: Odorology; chromatography; mass spectroscopy; olfactory